What undergraduates want in campus sexual assault prevention programming: Findings from a formative research study - Philyaw-Kotov, Meredith L.; Walton, Maureen A.; Brenneman, Brianne; Gleckman-Krut, Miriam; Davis, Alan K.; Bonar, Erin E. (Journal of American college health, 2023)
Campus sexual assault (SA) prevention programs are widely implemented, despite few having strong empirical support. To inform the development and refinement of prevention programs, we collected pilot qualitative data to capture undergraduates' perspectives regarding desirable program characteristics. Undergraduates completed an audio-taped interview (n = 19) or a focus group (n = 16) in June - November 2016. We double-coded transcripts for a priori and emerging themes using NVivo 11. A third coder resolved disagreements; we assessed intercoder reliability using Cohen's Kappa. Participants preferred SA prevention programming to be delivered in-person to small, coed groups of unfamiliar students. Students preferred programming with peer-facilitated, candid conversation about SA outcomes and prevention strategies. Participants also preferred for the tone of these training sessions to match the serious subject matter. Students' perceptions of desirable program characteristics differ somewhat from current evidence-based programs in several ways, highlighting important future directions for SA prevention research.